RANCANGAN APLIKASI ANALISA KUALITATIF DAN KUANTITATIF REKAM MEDIS PASIEN RAWAT INAP MENGGUNAKAN MICROSOFT EXCEL DI RUMAH SAKIT DI KOTA PADANG - Dewi Mardiawati; Linda Handayuni; Siti Handam Dewi; Maudy Ikhlasul Amal (Ensiklopedia of Journal, 2023)
Qualitative and quantitative analysis often found the number of incomplete medical records, analytical reports based on daily recaps, manual data input, and processing of the percentage of data that did not exist. So, medical record analysis requires database Microsoft Excel Fast and accurate Excel VBA programming language. The purpose of this study was to determine the database design for qualitative and quantitative analysis of inpatients using Microsoft Excel in the RSJ. Prof. Hb Saanin Padang. The type of research used is Research and development. In May – June 2022. The number of informants is 2 people and this study uses in-depth interview guidelines. The results showed that in the qualitative analysis database component there were 6 components and 15 data, while in the quantitative there were 4 components and 30 data. The person in charge of filling out the database is one officer. The database design uses UML including, Usecase, class and activity with VBA Excel programming language. The use of a database using Microsoft Excel has been tested and is in accordance with the hospital format. Based on the results of the study, it can be concluded that the database design is in accordance with the hospital format. It is hoped that the database design can be used by hospitals and this research can be continued by further researchers.